Penegakan Hukum terhadap Pelaku Lesbian dan Gay di Kota Palopo: Perspektif Hukum Islam - Magfirah, Adinda Cahya; Kurniati, Kurniati; Ahmad, La Ode Ismail; Rahayu, Sri (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This study aims to analyze law enforcement against lesbian and gay perpetrators in Palopo City through the perspective of Islamic law, by focusing on the basis of Islamic law that regulates homosexual behavior, law enforcement mechanisms, and social responses and challenges that arise in practice. This research was conducted to understand the principles of Islamic law applied in a modern context, especially in dealing with the issue of Lesbian and Gay in Palopo City. The research method used is qualitative with a case study approach, where data is collected through in-depth interviews with religious leaders, law enforcement officials, and Lesbian and Gay perpetrators, as well as analysis of Islamic legal documents and local regulations. The results of the study show that Islamic law expressly prohibits homosexual practices based on the postulates of the Qur'an and Hadith, but its implementation in Palopo City faces various obstacles, such as the lack of specific regulations, resistance from lesbian and gay perpetrators. In addition, the study reveals the tension between Islamic law enforcement and human rights, which poses a dilemma for both the government and society. This research is expected to be a consideration for policymakers and stakeholders in formulating more inclusive and equitable regulations.